2018
DOI: 10.1038/s41598-018-31584-2
|View full text |Cite
|
Sign up to set email alerts
|

Class II histone deacetylases require P/Q-type Ca2+ channels and CaMKII to maintain gamma oscillations in the pedunculopontine nucleus

Abstract: Epigenetic mechanisms (i.e., histone post-translational modification and DNA methylation) play a role in regulation of gene expression. The pedunculopontine nucleus (PPN), part of the reticular activating system, manifests intrinsic gamma oscillations generated by voltage-dependent, high threshold N- and P/Q-type Ca2+ channels. We studied whether PPN intrinsic gamma oscillations are affected by inhibition of histone deacetylation. We showed that, a) acute in vitro exposure to the histone deacetylation Class I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…The fact that the PPN modulates both waking and REM sleep, the two states with prominent EEG gamma band activity, suggests that TSA blockade of intrinsic membrane gamma oscillations eliminates a major process subserved by gamma band frequency activity, arousal. Our discovery suggests that this constant flow of continuous sensory information through the induction of gamma oscillations may be modulating the transcription of genes in PPN neurons . This represents a potential neuroepigenetic mechanism not previously considered, but which carries significant implications.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…The fact that the PPN modulates both waking and REM sleep, the two states with prominent EEG gamma band activity, suggests that TSA blockade of intrinsic membrane gamma oscillations eliminates a major process subserved by gamma band frequency activity, arousal. Our discovery suggests that this constant flow of continuous sensory information through the induction of gamma oscillations may be modulating the transcription of genes in PPN neurons . This represents a potential neuroepigenetic mechanism not previously considered, but which carries significant implications.…”
Section: Resultsmentioning
confidence: 73%
“…Our results showed that, (a) acute in vitro exposure to the histone acetylation inhibitor trichostatin A (TSA) led to the elimination of high threshold, voltage-dependent Ca 2+ channel-mediated intrinsic membrane oscillations, specifically in the gamma band range but not lower frequencies, (b) pre-incubation with TSA led to a similar decrease specifically in gamma band oscillations, (c) a significant reduction in Ca 2+ currents was elicited by the same histone acetylation inhibitor, d) a HDAC Class I inhibitor, MS275, failed to affect intrinsic gamma oscillations in PPN neurons, and e) a HDAC Class IIb inhibitor, MC1568, blocked gamma oscillations. 88 These results suggest that there is a specific effect on gamma band oscillations when histone deacetylation via HDACIIb is blocked, suggesting that gamma oscillations related to arousal could be modulated by the balance between histone acetylation and deacetylation.…”
Section: Neuroepigenetic Modulation Of Ppn Neuronsmentioning
confidence: 81%
See 3 more Smart Citations